2016
DOI: 10.1371/journal.pone.0151358
|View full text |Cite
|
Sign up to set email alerts
|

Supply- and Demand-Side Factors Influencing Utilization of Infant and Young Child Feeding Counselling Services in Viet Nam

Abstract: Adequate utilization of services is critical to maximize the impact of counselling on infant and young child feeding (IYCF), but little is known about factors affecting utilization. Our study examined supply- and demand-side factors associated with the utilization of IYCF counselling services in Viet Nam. We used survey data from mothers with children <2y (n = 1,008) and health staff (n = 60) from the evaluation of a program that embedded IYCF counseling into the existing government health system. The frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Another striking feature of the difficult access to health services is related to the working status of the Brazilian population, as those who had an occupation reported greater difficulty in using these services. The incompatibility between the working hours of most health services and the working hours of users contributes REV BRAS EPIDEMIOL 2021; 24: E210004 to perpetuating the disparities in access and the ignorance about their health, which can result in negative self-rated health 26,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Another striking feature of the difficult access to health services is related to the working status of the Brazilian population, as those who had an occupation reported greater difficulty in using these services. The incompatibility between the working hours of most health services and the working hours of users contributes REV BRAS EPIDEMIOL 2021; 24: E210004 to perpetuating the disparities in access and the ignorance about their health, which can result in negative self-rated health 26,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Past studies evaluating women's behavior toward IYCF practices in Kenya have focused on variety of factors, including socioeconomic aspects, with attention to HIV-AIDS status of mothers (Dasgupta et al 2017;Gewa and Leslie 2015;Kimani-Murage et al 2013;Wanjiku et al 2015;Wanjohi et al 2017); community level factors including access to health care facilities and community worker's incentive system (Nguyen et al 2016); parental role in decision-making and care practices (Chintalapudi et al 2017); intrahousehold factors including caregivers' competence (Schneider et al 2017) and the policy environment (Sanghvi et al 2016). Further, Issaka, Agho, and Renzaho (2017), Habtewold, Islam, and Sharew et al (2017), and Ogbo, Page, and Idoko et al (2015) use meta-analysis to examine the effect of multiple factors on IYCF.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Ethiopia showed that only 10.75% children aged 6-23 months received appropriate complementary feeding (12). In Vietnam, <20% of infants are exclusively breastfed in the first 6 months, and complementary foods are often introduced too early and tend to be of poor quality (13). Study conducted in Bangladesh showed that3 out of 5 children are currently undernourished, despite improving food availability (14).…”
Section: Discussionmentioning
confidence: 99%